Hubungan Gaya Kepemimpinan Kepala Ruangan Dengan Penerapan Budaya Keselamatan Pasien Di Rumah Sakit Murni Teguh Medan - Pane, Pebriana; Banjarnahor, Seriga (STIKes Murni Teguh, 2025)
The World Health Organization (WHO) states that patient safety is a serious global public health issue. Medical errors can be caused by both system and human factors. The purpose of this study was to determine the relationship between the leadership style of the ward head and the implementation of patient safety culture at Murni Teguh Hospital, Medan. This research method is descriptive with a cross-sectional design, a total of 60 respondents, sampling using accidental sampling technique with a sample of 60 respondents, using observation sheets and questionnaires. The results of the study that has been conducted found that the leadership style of the ward head at Murni Teguh Hospital is mostly moderate (29 people), a minority of high (14 people), and the patient safety culture at Murni Teguh Hospital is mostly quite good (27 people), and a minority of good (16 people). With the results of the bivariate analysis using the Chis-square test obtained a p value = 0.002, so p-value = 0.002 < α (0.05), thus there is a relationship between the leadership style of the ward head and the implementation of patient safety culture at Murni Teguh Hospital, Medan. This shows statistically that there is a significant relationship between leadership style and the implementation of patient safety culture.